AVOID Game as Implementation of Pancasila Student Profile Strengthening Project - Diah Ayu Praharani; Pramudyani, Avanti Vera Risti; Intan Puspitasari; Febritesna Nuraini (Universitas Pendidikan Ganesha, 2025)
Limited self and environmental awareness makes children vulnerable to abduction; therefore, from an early age they need to be equipped with safety knowledge in line with the Pancasila Student Profile Strengthening Project (P5). This study aims to analyze the application of P5 principles through the AVOID Game project in kindergarten. This study aims to analyze the application of P5 principles in the implementation of the Avoid Game project in kindergarten. The research employed a descriptive qualitative approach with a case study design. The subjects involved were the principal, teachers, parents, and kindergarten students. Data were collected through interviews, observations, and documentation. Data analysis followed Sugiyono’s model, including data collection, data display, data reduction, categorization, and construction. Data validation was conducted using technique triangulation involving interviews, observations, and documentation. The findings indicate that the Avoid Game, when implemented with holistic, contextual, child-centered, and explorative principles, can provide knowledge and understanding of self-awareness, recognizing close and trusted individuals, distinguishing potentially dangerous strangers, as well as responding appropriately and seeking help from safe people or places in risky situations. The novelty of this study lies in the integration of technology-based educational play (the Avoid Game) as a learning medium for implementing P5. Furthermore, this research has implications for learning practices, as it can be used as a variety of play activities that foster independence and support the six domains of child development, including religious and moral values, cognitive, language, motor, socio-emotional, and artistic development, both in extracurricular and intracurricular activities.